The Role of Integrated Marketing Communication On Consumer Decision-Making Process - Clarence Anthony Puspanathan; Ewe Yi Wen; Lee Ke Ni; Lee Tze Hui; Lee Xue Yee (USIM Press, 2024)
Vol. 6 No. 1 (2021): Jurnal Sains Insani